Possible vertical transmission of Chikungunya virus infection detected in the cord blood samples from a birth cohort in Vietnam - Mya Myat Ngwe Tun; Elizabeth Ajema Chebichi Luvai; Michiko Toizumi; Masako Moriuchi; Yuki Takamatsu; Shingo Inoue; Takeshi Urano; Minh Xuan Bui; Do Thai Hung; Hien-Anh Thi Nguyen; Dang Duc Anh; Lay-Myint Yoshida; et al. (Elsevier, 2024)
Background: Chikungunya virus (CHIKV) is an alphavirus (genus Alphavirus, family Togaviridae) that is primarily transmitted to humans by Aedes mosquitoes, and can be transmitted from mother to child. Little is known about CHIKV transmission in Vietnam, where dengue is endemic and Aedes mosquitoes are abundant. This study aimed to determine the prevalence and characteristics of vertical CHIKV infection in a birth cohort, and seroprevalence of anti-CHIKV antibodies with or without confirmation by neutralization tests among women bearing children in Vietnam. Methods: We collected umbilical cord blood plasma samples from each newly delivered baby in Nha Trang, Central Vietnam, between July 2017 and September 2018. Samples were subjected to molecular assay (quantitative real-time RT-PCR) and serological tests (anti-CHIKV IgM capture and IgG indirect enzyme-linked immunosorbent assay, and neutralization tests). Results: Of the 2012 tested cord blood samples from newly delivered babies, the CHIKV viral genome was detected in 6 (0.3%) samples by RT-PCR, whereas, 15 samples (0.7%) were anti-CHIKV-IgM positive. Overall, 18 (0.9%, 95% CI: 0.6-1.5) samples, including three positives for both CHIKV IgM and viral genome on RT-PCR, were regarded as vertical transmission of CHIKV infection. Of the 2012 cord blood samples, 10 (0.5%, 95% CI: 0.2-0.9) were positive for both anti-CHIKV IgM and IgG. Twenty-nine (1.4%, 95% CI: 1.0-2.1) were seropositive for anti-CHIKV IgG while 26 (1.3%, 95% CI: 0.8-1.9) of them were also positive for neutralizing antibodies, and regarded as seropositive with neutralization against CHIKV infection. Conclusion: This is the first report of a possible CHIKV maternal-neonatal infection in a birth cohort in Vietnam. The findings indicate that follow-up and a differential diagnosis of CHIKV infection in pregnant women are needed to clarify the potential for CHIKV vertical transmission and its impact in the newborn.